Phenothiazine and carbazole substituted pyrene based electroluminescent organic semiconductors for OLED devices. Issue 5 (8th January 2016) - Salunke, Jagadish K.; Wong, F. L.; Feron, Krishna; Manzhos, Sergei; Lo, Ming Fai; Shinde, Durgaprasad; Patil, Abhijeet; Lee, C. S.; Roy, V. A. L.; Sonar, Prashant; Wadgaonkar, Prakash P.
Abstract : Two new solution processable pyrene based electroluminescent organic semiconductors (PY-PH &PY-CA ) and their OLED performance reported. Abstract : Due to their easy availability, low cost and opportunities for exploiting reactions of bromo substituents, 1, 3, 6, 8-tetrabromopyrene has attracted major attention in the organic electronics community for designing and constructing novel classes of pyrene based organic semiconducting functional materials. In the present work, 1, 3, 6, 8-tetrabromo pyrene was transformed into the corresponding tetrasubstituted carbazole and phenothiazine derivatives using the classical Suzuki coupling reaction. These newly synthesized materials with a carbazole substituent (PY-CA ) and a phenothiazine substituent (PY-PH ) were characterised thoroughly and were successfully used as an active light-emitting layer in organic light emitting diodes which resulted in blue and green emission with promising device performance.PY-CA exhibited the maximum brightness at around 2500 cd m −2 and the power efficiency of 1.5 lm W −1 while that ofPY-PH exhibited 2116 cd m −2 and 0.45 lm W −1 respectively.